Cathelicidins Limit Intracellular Neospora caninum-Infection in Macrophages - Fiorani, Franco (2025)
Infections with the protozoan Neospora caninum cause abortion in cattle, likely due to the parasite’s replication and excessive inflammation in the placenta. Cathelicidins are host defense peptides known for their antimicrobial and immunomodulatory functions, but their role in N. caninum infections remains elusive. Using bone marrow-derived macrophages (BMDMs) isolated from mice expressing (wild-type, Camp+/+) and lacking (Camp−/−) cathelicidins, we investigated the role of endogenous cathelicidin in infections with N. caninum. We show that Camp−/− macrophages primed with lipopolysaccharide (LPS) had an increased number of intracellular N. caninum tachyzoites, and these macrophages released higher amounts of IL-1β and lactate dehydrogenase (LDH), a marker of cytotoxicity. These findings indicate that cathelicidins contribute to intracellular N. caninum control and inflammation by limiting the activation of the inflammasome, particularly under LPS-induced conditions. This insight reveals the immunomodulatory role of cathelicidins in controlling N. caninum-associated pathologies.